Розробка iot проекту за допомогою wi-fi модуля ESP8266 - Кравцов, К. Р. (ХНУРЕ, 2019)
Internet of things (IoT) is not something new: high technology companies and experts have been discussing the idea for many decades, and the first Internet-connected toaster was introduced to the conference in 1989. In essence, IoT is simple: it's about connecting devices over the Internet, allowing them to communicate with us, applications and with each other.Broadband Internet is becoming more widely available, the cost of connectivity decreases, more and more devices are created with Wi-Fi capabilities and sensors embedded in them, technology costs are reduced, and a smart phone is rapidly penetrating everywhere. All these things create the "perfect storm" for the IoT.